2013
DOI: 10.14499/indonesianjcanchemoprev4iss1pp483-487
|View full text |Cite
|
Sign up to set email alerts
|

Annona muricata's Leaves Ethanolic Extract Enhance p53 Expression in Rat Hepatic Cells Induced by Dimethylbenz(a)Anthracene (DMBA)

Abstract: Annona muricata or soursop contains acetogenin which can induce apoptosis in vitro and has cytotoxic effect. The study has been done to examine soursop leaves extract’s potency in vivo especially to induce apoptosis in 7,12-Dimethylbenz[a]anthracene (DMBA)-induced Sprague Dawley rats. The induction process was done twice a week for five weeks. The soursop leaves extract were given in three dosages, that are 200, 400, and 800 mg/kgBW for seventeen days after two weeks DMBA induction. Data analysis showed that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The histopathological analysis revealed insignificant hyperplastic lesions with no kareatin pearls compared with DBMA-treated animals suggesting a strong chemopreventive effect of graviola. Adelina R et al reported that EEL graviola (200, 400 and 800 mg/ kg BW) given to the Sprague Dawley rats for 17 days resulted in p53-dependent apoptosis of DMBA-induced liver cancer cells (67). Similar chemopreventive effects of MLE of graviola were reported by Rajesh M et al, in benzo[a]pyrene (BPa)-induced lung cancers (68).…”
Section: Graviola As a Chemopreventive Agentmentioning
confidence: 61%
“…The histopathological analysis revealed insignificant hyperplastic lesions with no kareatin pearls compared with DBMA-treated animals suggesting a strong chemopreventive effect of graviola. Adelina R et al reported that EEL graviola (200, 400 and 800 mg/ kg BW) given to the Sprague Dawley rats for 17 days resulted in p53-dependent apoptosis of DMBA-induced liver cancer cells (67). Similar chemopreventive effects of MLE of graviola were reported by Rajesh M et al, in benzo[a]pyrene (BPa)-induced lung cancers (68).…”
Section: Graviola As a Chemopreventive Agentmentioning
confidence: 61%